2002
DOI: 10.1128/iai.70.5.2598-2604.2002
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin G Monoclonal Antibodies toCryptococcus neoformansProtect Mice Deficient in Complement Component C3

Abstract: Passive administration of monoclonal antibodies (MAbs) to the capsular polysaccharide of Cryptococcus neoformans can alter the course of infection in mice. In a murine model of cryptococcal infection, immunoglobulin G1 (IgG1), IgG2a, and IgG2b switch variants of the anti-capsular 3E5 MAb prolong the survival of lethally infected mice, whereas the 3E5 IgG3 MAb does not protect and in some cases enhances infection, shortening the life spans of infected mice. We examined the role of complement component C3 in Ab-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(74 citation statements)
references
References 57 publications
(60 reference statements)
3
69
0
2
Order By: Relevance
“…Mechanisms by which Ab can affect a cell-mediated response include enhanced Ag presentation, changes in cytokine expression as a result of FcR activation, and increased expression of costimulatory molecules (35). Additional evidence for the dependence of IgG3 efficacy on other components of the immune system came from studies in complement-deficient mice, which showed that the disease-enhancing effect of IgG3 in C57BL/6J mice is dependent on the presence of C3 (36).…”
Section: Discussionmentioning
confidence: 96%
“…Mechanisms by which Ab can affect a cell-mediated response include enhanced Ag presentation, changes in cytokine expression as a result of FcR activation, and increased expression of costimulatory molecules (35). Additional evidence for the dependence of IgG3 efficacy on other components of the immune system came from studies in complement-deficient mice, which showed that the disease-enhancing effect of IgG3 in C57BL/6J mice is dependent on the presence of C3 (36).…”
Section: Discussionmentioning
confidence: 96%
“…We show that BALB/c and CBA/J mice, defined as moderately and highly resistant to C. neoformans infection (4), produce higher amounts of total IgG (mainly of the IgG 1 isotype) than the susceptible C57BL/6 mice. Protection mediated by exogenous IgG 1 anti-GXM specific mAbs has been shown in several studies (6,10); in contrast to non-protective IgG 3 mAbs directed to the same epitope (10), IgG1 antibodies have been previously reported as protective in experiments of passive transfer in the mouse model (23)(24)(25). In these studies, it was observed that the three strains of infected animals produced both IgG 2a and IgG 2b but at relatively lower levels, and there were no significant differences between strains (23)(24)(25).…”
Section: Discussionmentioning
confidence: 96%
“…Protection mediated by exogenous IgG 1 anti-GXM specific mAbs has been shown in several studies (6,10); in contrast to non-protective IgG 3 mAbs directed to the same epitope (10), IgG1 antibodies have been previously reported as protective in experiments of passive transfer in the mouse model (23)(24)(25). In these studies, it was observed that the three strains of infected animals produced both IgG 2a and IgG 2b but at relatively lower levels, and there were no significant differences between strains (23)(24)(25). Taken together, these results suggest that IgG 2a and IgG 2b do not play an important role in murine resistance or susceptibility to cryptococcosis in vivo.…”
Section: Discussionmentioning
confidence: 96%
“…(Fig. 1) The complement component C3 was found to be dispensable for the protection by these IgGs [67]. In addition, mouse background also shown to influence the protection given by IgG subclass antibodies [68] thus underscoring the complex relationship between the cellular and humoral components of the immune system.…”
Section: Demonstration Of Protective Role Of Antibodies In Fungal Infmentioning
confidence: 99%